(untitled) (FAVE Sección Ciencias Veterinarias, 2022)
Presurgical planning is vital both to improve the overall outcome of the procedure and to reduce surgical time, minimizing intra and postoperative complications. When approaching fractures in uncommon or infrequent areas, interdisciplinary work and technological image and 3D printing resources become great value tools. The goal of this work is to show, with a clinical case, how working on a 3D printed model allow us to develop an organized workplan, that looks for time optimization, anticipating possible complications, which results in better outcomes and life quality for the patient.